Un finale per Terre dissodate: (ri)scritture sceniche del romanzo kolchoziano - Mari, Emilio (Status Quaestionis, 2022)
The aim of this paper is to analyze the practices of theatrical adaptation of Mikhail Sho- lokhov’s Virgin Soil Upturned in the context of the rapidly changing Soviet politics and aesthetics of the early 1930s. Despite being acclaimed by the government as a model of the new Party-oriented peasant literature produced by professional writers, the novel perhaps scored its biggest success in peripherical amateur and spontaneous theaters, whose distan- ce from Moscow could still grant them a certain level of autonomy from the emerging canon of Socialist Realism. Especially if considered in the framework of the theoretical debates of literary journals, these plays show how, even after the Great Turn of 1929, So- viet theatres continued to be a social laboratory where propaganda discourse and popular taste, high and low genres mixed heterogeneously, before the totalitarian art paradigm would eventually prevail.